Prescription of pain medication in prisons: A comparative analysis of younger and older male prisoners. Issue 9 (21st June 2018) - Annaheim, Beatrice; Bretschneider, Wiebke; Handtke, Violet; Belardi, Angelo; Elger, Bernice S.
Abstract: Purpose: In prison populations, treating pain is particularly challenging, especially for the growing number of older prisoners. The objective was to find out about prevalence, frequency, and types of pain medications prescribed to older prisoners (≥50 years) in comparison with younger prisoners (<50 years). Methods: Data were collected in Switzerland as part of a study on ageing prisoners' health. Fifteen prisons (out of 26 of the total eligible population) agreed to take part, and data from medical records of 190 older and 190 younger male prisoners were analysed. Descriptive statistics on pain medication prescriptions (excluding drugs used in opioid dependence) were carried out and differences between the 2 age groups tested for statistical significance. Results: More than half of younger and older prisoners were prescribed pain medication during the past 180 days, while 10% of younger and 15% of older prisoners were prescribed pain medication on a daily basis. Nonsteroidal anti‐inflammatory drugs and "other analgesics and antipyretics" were most frequently prescribed. Significantly ( P  < .05), more younger than older prisoners were prescribed NSAIDs and drugs to treat muscle skeletal pain. Tramadol was the opioid most often prescribed. Conclusions: This is the first empirical study investigating prescriptions of pain medication in Swiss prisoners on a national level. It shows that nonopioid pain medication is an important part of health care provision inside prison, while there are only few prescriptions of strong opioids. Research is needed to investigate whether the standard set by the principle of equivalence is met regarding treatment of pain in prison.